(untitled) (Docentes 2.0 Journal, 2020)
The WebQuest is a didactic resource based on constructivist learning that is having great success in the educational context. However, there have been deficiencies when incorporating new technologies in the teaching-learning processes, specifically at the higher education level since there are no specific digital resources for the different subjects taught in the training of future undergraduate professionals. Therefore, in this study, the objective is to integrate the activity of WebQuest through the creation of the didactic instrument that allows the development of individual and collaborative skills both in the classroom and outside it, which allows the strengthening of the teaching and learning process in the higher education institution. This research uses a mixed approach that, through data collection instruments such as direct observation, literature review and survey, addressed 34 professionals in training at a higher level. This allows us to describe the importance of the use of this Webquest didactic instrument in the educational environment and how it favors the development of cognitive skills in students. Within the results of this research, the development of 6 Webquest instruments elaborated by workgroups formed by the 34 participants can be highlighted. It can be concluded that the implementation of this didactic instrument facilitates the didactic possibilities, which enhance the cognitive skills promoting critical thinking, generating significant learning through the creation of digital resources. Furthermore, it is necessary to suggest what to do to achieve all these advances is recommended to enhance the digital competences of the professionals in training.